Biomass and Carbon stock Assessment of Phanerophytes: A case study of Village Ecosystem used for Ecological Optimization to Mitigate Climate Change - Lahiri, Subhajit; Das, Monalisa; Chatterjee, Moumita (Indian Forester, 2019)
The present communication is based on Carbon sequestration potential of ten selected ligneous species which were predominant in the Rajhat village of Hooghly district. It was observed that Swietenia mahogani has highest carbon sequestration potential whereas Disoxylum costulatum has lowest potential. The correlation between GBH and height with carbon sequestration potential were determined which is positive while summing up it can be said that, the present work exhibit the pathway of aesthetic rejuvenation through landscape designing pledge with environmental optimization through CO2 sequestration with appropriate trees.